Gaya Bahasa Dakwah Gus Miftah di Pasar Kembang Yogyakarta: Analisis Isi Akun YouTube @GusMiftahOfficial - Siti Mariyam (Universitas Islam Negeri Madura, 2024)
This research examines in depth the preaching of Gus Miftah at Pasar Kembang Yogyakarta by highlighting two main problems, namely the message of preaching and the language style of Gus Miftah's preaching. This research uses a descriptive qualitative approach with content analysis research type. Content analysis is a research tool that concentrates on actual content and media characteristics, in this case the preaching content of Gus Miftah @GusMiftahOfficial episode